The Effect of Using Tween 80 as A Foaming Agent on Drying Corn-Yogurt Using the Foam-Mat Method - Nur Aini; Ratih Tiara Dewi; Pepita Haryanti; Vincentius Prihananto; Anita Khairunnisa; Budi Sustriawan; Hadana Sabila Arsyistawa; Annisa Fitriati; Indarto Indarto; Banun Diyah Probowati (Journal of Agri-Food Science and Technology, 2026)
The public's appetite for foods that are both satiating and offer distinct functional benefits has driven an increasing demand for functional foods. Corn yogurt is a type of functional food now under development. Corn yogurt is a fermented product with a relatively high moisture content and low protein content. To increase the protein content, it is fortified with spirulina and soy protein isolate. To extend its shelf life, corn yogurt is made into powder form using the foam mat drying method. This study contributes to determining the effect of Tween 80 concentration as a foaming agent on the physicochemical, functional, and sensory properties of corn-yogurt powder. Corn yogurt fortified with spirulina and soy protein isolate was dried using the foam-mat method, with maltodextrin and Tween 80 as foaming agents. The foaming agents were mixed for 8 minutes until foaming occurred, and the fortified yogurt was incorporated using the folding method. The mixture was poured onto a glass plate and dried in a cabinet dryer at 60 °C for 8 h. The dried sample was ground and sieved through 80 mesh. The dried yogurt has a protein content of 4.08–4.329%. The pH of the corn yogurt was lower than the range specified by the Indonesian National Standard (3.54–3.62); hence, this product was sourer than typical yogurts. The best corn yogurt powder was prepared with 1.75% Tween 80 and had 72.67% antioxidant activity, 133.76 µg/100 g β-carotene, and 9.22×107 log CFU/g lactic acid bacteria. This fortified corn yogurt powder shows potential as an alternative functional food product because of its functional compounds and high protein content.